2017
DOI: 10.1088/1361-6587/aa576c
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten erosion by impurities and redeposition: focus on the magnetised sheath

Abstract: The effect of the magnetised sheath on the gross erosion and redeposition of tungsten is examined with an insight on impurity impact energy and angle. A complete treatment of the impact energy is performed leading to a scaling that differs from the usual 2k B T i +3Zk B T e formula. It is found that even if the energy distribution at the sheath entrance strongly differs from this approximation, the discrepancy remains under 20% for the impact energy. The average impact angle of a set of impurities is calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…The magnetic field geometry and sheath structure are known to modify these impact distributions, and the angle and energy of the impacts greatly affects the probability for consequent sputtering (see Refs. [22,33,34] and references therein).…”
Section: Detailed Magnetic Shadowing Of the Densitymentioning
confidence: 99%
“…The magnetic field geometry and sheath structure are known to modify these impact distributions, and the angle and energy of the impacts greatly affects the probability for consequent sputtering (see Refs. [22,33,34] and references therein).…”
Section: Detailed Magnetic Shadowing Of the Densitymentioning
confidence: 99%
“…The effect of the sheath electric field on the subsequent trajectories can be characterized by the potential energy of tungsten impurities normalized to their kinetic energy [24]. This ratio can be considered as an effective sheath electric field, , ´-~), as discussed in [12]. As a consequence, the sheath electric field impacts the trajectories of heavy impurities like tungsten more dramatically than lighter impurities (figure 1(b)).…”
Section: Scaling Law For W Prompt Re-depositionmentioning
confidence: 99%
“…As a result of the large width of the sheath near divertor targets, a vast majority of tungsten impurities sputtered from divertor PFMs are ionized multiple times within the sheath and accelerated back toward the divertor surfaces by the sheath electric field over a distance comparable to the Larmor radius, a process known as prompt re-deposition [6][7][8]. The complexity of predictive models for tungsten prompt re-deposition and net erosion in divertors has been noted [9][10][11][12][13][14][15]. Experimental measurements of tungsten net erosion in divertors of various devices, such as JET [16], DIII-D [17][18][19], ASDEX-Upgrade [20] or WEST [21], are generally well-reproduced by numerical models, e.g., ERO [22].…”
Section: Introductionmentioning
confidence: 99%
“…The ion trajectory in the sheath has been modeled with equation-of-motion (EOM) [16,25], ERO Monte Carlo [12,26,27], kinetic particle-in-cell (PIC) [28], and large gyro-orbit model [9] calculations. A calculation reported that the ion angle distribution (IAD) in the sheath varies drastically by changing the sheath length [25].…”
Section: Introductionmentioning
confidence: 99%